Green tea (Camellia sinensis) extract reduces peptic ulcer induced by Helicobacter pylori in sprague dawley rats - Marhanis Salihah Omar; Nur Nadiana Adnan; Endang Kumolosasi; Norazrina Azmi; Noor Safwah Damanhuri; Fhataheya Buang (Penerbit Universiti Kebangsaan Malaysia, 2020)
The study was conducted to evaluate the anti-peptic ulcer activity of ethanol extract of Camellia sinensis (green tea) induced by Helicobacter pylori in Sprague Dawley rats. The standard regimen of anti-peptic ulcer agents, clarithromycin 30 mg/kg, amoxicillin 30 mg/kg and esomeprazole 3 mg/kg used as the positive control. The rats divided into 6 groups (n = 6), normal control, vehicle control (2% of tragacanth suspension), positive control for preventive and treatment groups, preventive and treatment groups were given 50 mg/kg orally of green tea extract for 14 days before and after inoculation (as prevention and treatment, respectively) with 5×108 CFU/mL H. pylori suspension orally twice daily for 7 days. Anti-peptic ulcer activity was evaluated based on the pH of gastric juice, ulcer score and body weight of rats. The results demonstrated that the use of green tea for prevention or treatment showed a significant difference (p<0.001) in reducing the pH of gastric juice 3.88 ± 0.09 and 5.74 ± 0.08, respectively, compared to vehicle control 5.85 ± 0.12. Meanwhile, vehicle control rats had high significantly reduced body weight when compared with all groups treated. The preventive and the treatment groups showed significantly reduce in ulcer score to 0.50 ± 0.18 (p<0.01) and 0.83 ± 0.10 (p<0.05), respectively, compared to vehicle control 1.50 ± 0.22. Meanwhile, it was comparable to the positive control. In conclusion, H. pylori suspension 5×108 CFU/mL given orally twice daily for seven days able to induce ulcer in Sprague Dawley rats, and the green tea extract 50 mg/kg was comparable to the standard regimen as anti-peptic ulcer agent.